2022
DOI: 10.3389/fmed.2022.850002
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Perfusion of Autologous Platelet-Rich Plasma Before Frozen-Thawed Embryo Transfer Improves the Clinical Pregnancy Rate of Women With Recurrent Implantation Failure

Abstract: ObjectiveTo evaluate whether the intrauterine perfusion of platelet-rich plasma (PRP) before frozen-thawed embryo transfer (FET) improves the pregnancy outcomes of patients with repeated implantation failure (RIF).MethodsThis retrospective study included 288 infertile women with RIF after undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) treatment from October 1, 2019, to January 1, 2021, at Qingdao Women and Children's Hospital. Patients were divided into two groups according to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…It has been reported that PRP can improve clinical pregnancy rates and endometrium thickness in patients with RIF ( 231 ). The benefit of PRP on implantation rates in patients with RIF has been confirmed by other studies ( Table 1 ) ( 232 , 233 , 243 ). Thus, PRP is a promising treatment option.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It has been reported that PRP can improve clinical pregnancy rates and endometrium thickness in patients with RIF ( 231 ). The benefit of PRP on implantation rates in patients with RIF has been confirmed by other studies ( Table 1 ) ( 232 , 233 , 243 ). Thus, PRP is a promising treatment option.…”
Section: Discussionsupporting
confidence: 74%
“…The release of platelet-derived growth factors, vascular endothelial growth factors, transforming growth factors, and epidermal growth factors from activated platelets results in angiogenesis, cell (231). The benefit of PRP on implantation rates in patients with RIF has been confirmed by other studies (Table 1) (232,233,243). Thus, PRP is a promising treatment option.…”
Section: Platelet-rich Plasmamentioning
confidence: 80%
“…Tables S 2 and S 3 summarized the main characteristics of the included RCTs and non-RCTs. Twenty-seven studies were included in our analysis: 13 were RCTs [ 18 30 ], 5 was prospective cohort [ 17 , 31 35 ], 4 were prospective single-arm [ 35 38 ], and 5 were retrospective analysis [ 39 44 ]. All the studies were single centers except Kusumi [ 35 ], which was conducted in 7 fertility clinics.…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al [38] retrospectively evaluated 288 women with a RIF history (three or more consecutive failed embryo implantations with good-quality embryos, defined as at least six cleavage-stage embryos or three blastocysts). In total, 138 patients with PRP treatment and 150 patients who did not receive treatment were compared and the implantation, clinical pregnancy, and live birth rates were higher in the PRP group.…”
Section: Prp Use In Rifmentioning
confidence: 99%